2015
DOI: 10.1016/j.jsbmb.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Novel activities of CYP11A1 and their potential physiological significance

Abstract: CYP11A1, found only in vertebrates, catalyzes the first step of steroidogenesis where cholesterol is converted to pregnenolone. The purified enzyme, also converts desmosterol and plant sterols including campesterol and β-sitosterol, to pregnenolone. Studies, initially with purified enzyme, reveal that 7-dehydrocholesterol (7DHC), ergosterol, lumisterol 3, and vitamins D3 and D2 also serve as substrates for CYP11A1, with 7DHC being better and vitamins D3 and D2 being poorer substrates than cholesterol. Adrenal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
235
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 260 publications
(242 citation statements)
references
References 121 publications
(258 reference statements)
6
235
0
1
Order By: Relevance
“…Over 12 years we have documented the existence of new pathways of vitamin D3 metabolism started by the action of CYP11A1 and further modified by the actions of CYP27B1, CYP27A1, CYP24A1 and CYP3A4, generating at least 21 hydroxymetabolites with additional ones still to be experimentally defined (Table 1) [43, 50]. At least 13 of them are endogenously produced [72].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 12 years we have documented the existence of new pathways of vitamin D3 metabolism started by the action of CYP11A1 and further modified by the actions of CYP27B1, CYP27A1, CYP24A1 and CYP3A4, generating at least 21 hydroxymetabolites with additional ones still to be experimentally defined (Table 1) [43, 50]. At least 13 of them are endogenously produced [72].…”
Section: Resultsmentioning
confidence: 99%
“…However, the expression of CYP11A1 in peripheral tissues, albeit at low levels, has now been documented [43] and alternative substrates to cholesterol have been identified experimentally, such as 7DHC, vitamins D2 and D3, ergosterol and lumisterol [4449]. Additionally, the possibility of other sterol/secosteroidal compounds serving as substrates has been predicted theoretically based on molecular modeling [50]. …”
Section: New Pathways Of Vitamin D Activationmentioning
confidence: 99%
“…It has been established in the last decade that CYP11A1 (also known as cytochrome P450scc) can metabolize vitamin D3 to produce many novel mono- and poly-hydroxyvitamin D metabolites, the major ones being 20 S -hydroxyvitamin D3 [20(OH)D3] and 20 S ,23-dihydroxyvitamin D3 [20,23(OH) 2 D3] [818]. This pathway was initially elucidated from in vitro studies with purified bovine CYP11A1, and more recently has been demonstrated to occur in keratinocyte cell cultures and in fragments of adrenal glands and human placenta incubated with vitamin D3 [16, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…This pathway was initially elucidated from in vitro studies with purified bovine CYP11A1, and more recently has been demonstrated to occur in keratinocyte cell cultures and in fragments of adrenal glands and human placenta incubated with vitamin D3 [16, 18, 19]. Most recently, 20(OH)D3 and 20,23(OH) 2 D3 have been detected at relative levels similar to the classical 25(OH)D3 and 1,25(OH) 2 D3 in human epidermal tissue [20], confirming their production in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Steroidogenesis is initiated by CYP11A1, which cleaves the side chain of cholesterol, thereby producing pregnenolone, the common precursor for all steroid hormones. In addition, CYP11A1 can convert a variety of other sterol derivatives, as well as vitamins D 2 and D 3 (Slominski et al, 2015) and a set of endogenous steroid intermediates (Mosa et al, 2015). CYP21A2 generates the substrates for gluco-and mineralocorticoid biosynthesis by its 21-hydroxylase activity.…”
Section: Introductionmentioning
confidence: 99%